Reconstruction of Female Urethra with Tubularized Anterior Vaginal Flap - Ajit Sawant; Gaurav Vinod Kasat; Vikash Kumar; Prakash Pawar; Ashwin Tamhankar; Sumit Bansal; Lomesh Kapadnis; Abhishek Savalia (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Female urethral injury is a rare disease. Causes of urethral injuries are prolonged obstructed labour, gynaecological surgeries like vaginoplasty and post traumatic urethral injuries. The present study was conducted to evaluate outcome of female urethral reconstruction using tubularized anterior vaginal wall flap covered with fibroadipose martius flap and autologous fascia sling in patients with urethral loss. Aim: Aim of study was to evaluate outcome of reconstruction of female urethra with tubularized anterior vaginal flap. Materials and Methods: Retrospective analysis of all the patients with complete urethral loss was done from August 2008 to July 2015. Total seven patients were included in study. All patients presenting with total urethral loss were included. These patients were treated with tubularized anterior vaginal flap. Neourethra was covered with Martius labial flap and autologous fascia lata or rectus abdominis fascia sling. Most common cause of urethral loss was obstructed labour (57.1%). Postoperatively patients were assessed for continence, urine flow rate, ultrasound for upper urinary tract and post void residue. Results: Mean operative time was 180 minutes (160-200 minutes) and Intraoperative blood loss was 220ml (170-260 ml). Mean postoperative hospital stay was eight days (seven to nine days) Mean post surgery maximum urine flow rate was more than 15ml/sec (6.7-18.2ml/sec) and mean post void residual urine was 22.5ml (10-50ml). Median follow-up time was 35 months. All patients were catheter free and continent post three weeks of surgery except one patient who developed mild stress urinary incontinence. One patient developed urethral stenosis which was managed by intermittent serial urethral dilatation. Conclusion: Female neourethral reconstruction with tabularized anterior vaginal flap and autologous pubovaginal sling is feasible in patients of total urethral loss with success rate of approximately 86%. It should be considered in patients of complete urethral loss with adequate healthy vaginal tissue.